2021
DOI: 10.1001/jamanetworkopen.2021.8184
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Simulation of the Exposure Notification Cascade for Digital Contact Tracing of SARS-CoV-2 in Zurich, Switzerland

Abstract: IMPORTANCE Digital contact tracing (DCT) apps have been released in several countries to help interrupt SARS-CoV-2 transmission chains. However, the effect of DCT on pandemic mitigation remains to be demonstrated. OBJECTIVE To estimate key populations and performance indicators along the exposure notification cascade of the SwissCovid DCT app in a clearly defined regional and temporal context. DESIGN, SETTING, AND PARTICIPANTSThis comparative effectiveness study was based on a simulation informed by measured d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 17 publications
3
36
0
Order By: Relevance
“…One potential advantage of the app is that it may be even more effective in times when case numbers are high leading to capacity issues in MCT. However, this requires that app coverage is sufficient and an efficient process is in place to initiate the notification cascade [ 13 , 22 ]. Thus, our findings may underestimate the effectiveness of the SwissCovid app in situations where MCT is overwhelmed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One potential advantage of the app is that it may be even more effective in times when case numbers are high leading to capacity issues in MCT. However, this requires that app coverage is sufficient and an efficient process is in place to initiate the notification cascade [ 13 , 22 ]. Thus, our findings may underestimate the effectiveness of the SwissCovid app in situations where MCT is overwhelmed.…”
Section: Discussionmentioning
confidence: 99%
“…Third, DPT has a wider reach than MCT because it does not rely on the infected individual’s recollection of his or her encounters. However, DPT apps are complex interventions involving multiple, sequential steps and specific actions by app users to exert their effect (notification cascade [ 13 ], Supplementary File 1 ). To date, the possible impact of DPT apps on pandemic mitigation is only partially understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular interest is placed on the added benefit of exposure notifications from digital proximity tracing apps relative to manual contact tracing in containing nonhousehold spread [ 11 , 12 ]. For example, recent studies in England [ 13 ] and Switzerland [ 14 ] revealed an average of 4 exposure notifications per index case were triggered by infected app users, which highlights the considerable breadth of digital proximity tracing apps over traditional manual contact tracing. However, attributing the contribution of digital proximity tracing apps on the mitigative actions taken by exposure notification recipients is a challenge due to inconsistent data availability [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, evaluations are needed to demonstrate whether single parts and the whole system of DPT perform well from a technical perspective, but also whether DPT helps to contain transmission chains (6). First datadriven studies of DPT effectiveness have started to emerge only recently (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%